Time-varying consumption correlation and the dynamics of the equity premium: Evidence from the G-7 countries - Asani Sarkar; Lingjia Zhang (Federal Reserve Bank of New York, 2004)
We examine the implications of time variation in the correlation between the equity premium and nondurable consumption growth for equity return dynamics in G-7 countries. Using a VAR-GARCH (1,1) model, we find that the correlation increases with recession indicators such as above-average unemployment growth and with proxies for stock market wealth. The combined effect is that the correlation increases during a recession. We find that the effect of a countercyclical correlation is that the equity premium, Sharpe ratio, and risk aversion are also generally countercyclical. These findings survive several robustness checks such as allowing the mean return to depend on its conditional variance and controlling for lower consumption volatility during the post-1990 period. The evidence is stronger for countries that have larger stock market capitalization relative to GDP. Our results show the importance of combining financial and macroeconomic indicators for explaining time variation in the consumption correlation and the equity premium.
Keywords: G12; G15; 330; Risikoprämie; Gesamtwirtschaftlicher Konsum; G-7-Staaten